THE IMPACT OF NEUROSCIENCE-BASED MINDFULNESS TRAINING ON MENTAL HEALTH IN FUTURE PSYCHOLOGISTS - Lazorko, Olha (My University, 2024)
Purpose. This study investigates the effectiveness of a neuroscience-based mindfulness training program on emotional states, self-compassion traits and well-being status among psychology students during an 8-week intervention. The work focuses on developing emotional regulation, decreasing stress and depression, and increasing self-compassion and mindfulness — all of which are crucial skills for professional practice. Methods. This pilot study included fifty psychology students (M = 23.5, SD = 2.8) who were assessed using the DASS-21 for stress, anxiety, depression and Self-Compassion Scale for self-kindness, mindfulness and related traits before and after a special training program along with the BBC-SWB questionnaire for psychological, physical and subjective well-being. Statistical analyses such as paired t-tests, correlation analysis and hierarchical regression were used to assess the intervention's effectiveness and explore predictive relationships among variables. Results. The program was associated with significant reductions in anxiety, stress, and depression and increases in self-kindness, mindfulness, and psychological well-being. Given that emotional states and self-compassion traits function as mutually reinforcing factors, correlations provided evidence based on the holistic benefits of the program. Hierarchical regression analysis showed that both pre-intervention anxiety (β = 0.45, p < 0.001) and self-kindness (β = 0.35, p = 0.05) significantly predicted psychological well-being after the intervention. These variables combined explained 52% of the outcome variance (R² = 0.52, p < 0.001). Mindfulness explained an additional 17% variance beyond all other variables combined, affirming its role as a transformational variable within the model. Conclusions. This mindfulness training, based on neuroscience principles and research findings, is designed to decrease psychological suffering and enhance psychological resilience and self-compassion. The results call for incorporating such training within psychology educational programs, thus enhancing personal health and professional competence. Longitudinal studies investigating the long-term effects of mindfulness practices and their use in a broader range of populations are warranted for future research.
Keywords: emotional regulation; mindfulness training; self-compassion; psychological well-being